Atypical Large Vessel Vasculitis Presenting With Cholestatic Liver Abnormalities: Case-Based Review. Issue 8 (December 2021) - Sangha, Sameet; Lenert, Aleksander; Dawoud, Salma; Kaur, Aneet; Yazan, Hasan; Voigt, Michael D.; Lenert, Petar
Abstract : Abstract: Clinicians usually easily recognize cranial manifestations of giant cell arteritis (GCA) such as new-onset headache, jaw claudication, scalp tenderness, and abrupt changes in visual acuity or blindness; however, when presented with an aberrant clinical course, the diagnosis becomes more elusive. In addition to temporal arteries and other extracranial branches of the carotid arteries, large vessel vasculitis (LVV) can also affect other blood vessels including coronary arteries, aorta with its major branches, intracranial blood vessels, and hepatic arteries. Over time, the scope of the symptoms typically associated with LVV has broadened and includes cases of fever of unknown origin accompanied with other constitutional symptoms that can mimic a range of neoplastic and infectious diseases. In up to half of patients with atypical LVV, liver enzyme level elevations with a cholestatic pattern have been observed. Alkaline phosphatase level and γ-glutamyl transferase level elevations tend to be more prevalent in those LVV patients with vigorous inflammatory responses, particularly in those with fever and other nonspecific constitutional symptoms. These patients also have more profound anemia and thrombocytosis. With the exception of rare instances of vasculitides and granulomas affecting the liver tissue, liver biopsy is generally of little help and primarily shows nonspecific changes of fatty liver. In this article, we review 3 patients who were eventually diagnosed with atypical LVV. The diagnosis was confirmed with temporal artery biopsy in 2 patients and with positron emission tomography/computed tomography in 1 patient. The common hepatic abnormality observed in all patients was the elevation of alkaline phosphatase level, which tended to respond rapidly to initiation of immunosuppressive treatment.